Genotyping and physiological characteristics of Acanthamoeba isolated from beaches in Phuket Province, Thailand - NARUMON BOONMAN; CHANATE WANNA; JARUWAN CHUTRTONG; SRILERT CHOTPANTARAT; SIRIPHAN BOONSILP (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Boonman N, Wanna C, Chutrtong J, Chotpantarat S, Boonsilp S. 2022. Genotyping and physiological characteristics of Acanthamoeba isolated from beaches in Phuket Province, Thailand. Biodiversitas 23: 4377-4384. Acanthamoeba is widely distributed in water, soil, dust and air. Beaches are popular tourist destinations for water-related activities while they can also be reservoirs for Acanthamoeba to humans. This study aimed to determine the genotyping of Acanthamoeba in the beach environment and characterized their pathogenicity potential. A total of 63 samples were collected from six beaches in Phuket Province, Thailand. Twenty-one samples of each source including wet sand, dry sand and seawater, were collected and cultivated on 2% non-nutrient agar coated with heat-killed Escherichia coli. Acanthamoeba was found in 100% (n=21) wet sand, 52.4% (n=11) dry sand and 14.3% (n=3) seawater. Sequence analysis of the GTSA.B1 region in 18S rRNA revealed that 83.9% of sequenced isolates belonged to the T5 genotype and 16.1% belonged to the T4 genotype. The T5 genotype was predominant, differing from other reports of Acanthamoeba prevalence in natural sources. In vitro thermal and salt-tolerance showed that all isolates had growth rates similar to clinical Acanthamoeba isolates. This research was undertaken to increase awareness of human eye and brain infections caused by Acanthamoeba on beaches. Further studies on these Acanthamoeba isolates are still required such as co-culture assay between the trophozoites and human cell lines to confirm their pathogenicity as well as their susceptibility to the chemotherapeutic agents.